Anterior cruciate ligament injuries in elite and high school rugby players: a 11-year review? - Takazawa, Y.; Nagayama, M.; Ikeda, H.; Kawasaki, T.; Ishijima, M.; Saita, Y.; Kaneko, H.; Kobayashi, Y.; Hada, S.; Kaneko, K. (The Physician and Sportsmedicine, 2015)
Objectives: Over a 11-year period, we investigated the incidence of anterior cruciate ligament (ACL) injuries and the clinical outcomes after ACL reconstruction with hamstring autografts in two homogenous cohorts of rugby players. Methods: Two teams, including those in elite (94 players) and high school (290 players) clubs, were followed. Results: Isolated ACL injuries occurred in 28 players (12 elite, 16 high school). The incidence during match play was 1.26 per 1000 player-hours (95% confidence interval [95% CI]: 0.48-2.05) among elite players and 0.97 per 1000 player-hours (95% CI: 0.30-1.64) among high school players. After ACL reconstruction, 26 players (12 elite, 14 high school) were successfully contacted for follow-up at a mean of 71.9 months. None (0%) of the elite and 4 (29%) of the high school players experienced graft ruptures. Seven (58%) elite and 10 (91%) high school players were fearful of reinjury; the mean time to overcome this fear was 6.1 ± 4.9 months among elite players and 17.5 ± 26.0 months among high school players. Conclusion: In conclusion, young rugby players experienced inferior outcomes after ACL reconstruction with hamstring autografts compared with their older counterparts.